O imposto sobre operações financeiras nas operações de crédito: sua extrafiscalidade no contexto do superendividamento - SOUSA, Carlos Vinícius Sousa de (2024)
The Tax on Financial Operations (TFO) is a tax of an eminently extra-fiscal nature, with a view to the objective of maintaining the national economy and the predisposition to induce taxpayers to a certain social purpose. In a context of over-indebtedness due to exacerbated credit, it is necessary to make maximum use of the extra-fiscal nature of such a tax. Thus, we seek to understand how greater taxation on credit can reduce this current scenario in Brazil. The first part of the research establishes a legal apparatus on the TFO, addressing the fiscal and extra fiscal nature of the tax. In a second step, there is a discussion about overindebtedness resulting from the irresponsible supply of credit, a frequent practice of many financial institutions. The third topic concerns the TFO rate, based on the exception to the principle of strict legality. In the end, the way in which the Financial Operations Tax can help control personal over-indebtedness in the country is determined.